2006
DOI: 10.1177/0361198106197200113
|View full text |Cite
|
Sign up to set email alerts
|

Transit Ridership Model Based on Geographically Weighted Regression

Abstract: This paper describes the development of a geographically weighted regression (GWR) model to explore the spatial variability in the strength of the relationship between public transit use for home-based work (HBW) trip purposes and an array of potential transit use predictors. The transit use predictors considered include demographics and socioeconomics, land use, transit supply and quality, and pedestrian environment. The best predictors identified through model estimation include two global variables (regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 2 publications
1
33
0
Order By: Relevance
“…Additionally, the geographically weighted regression (GWR) was constructed, and it references a family of "spatially adjusted" regressions to solve the problem of spatial autocorrelation, which is common in spatial data [10]. Chow et al [29] developed GWR models in the level of region with 2000 TAZs, and two subregions with 555 and 215 TAZs for Broward Country, Florida. Chow found that GWR models had better performance than the OLS method, and subregional GWR models had better fit than regional GWR model.…”
Section: Direct Ridership Forecastingmentioning
confidence: 99%
“…Additionally, the geographically weighted regression (GWR) was constructed, and it references a family of "spatially adjusted" regressions to solve the problem of spatial autocorrelation, which is common in spatial data [10]. Chow et al [29] developed GWR models in the level of region with 2000 TAZs, and two subregions with 555 and 215 TAZs for Broward Country, Florida. Chow found that GWR models had better performance than the OLS method, and subregional GWR models had better fit than regional GWR model.…”
Section: Direct Ridership Forecastingmentioning
confidence: 99%
“…GWR has become a more commonly used technique in urban studies by addressing diverse urban problems. GWR applications have widespread in the fields of ecology (Zhang & Shi, 2004;Kimsey, https://doi.org/10.15405/epsbs.2020.03.03.90 Corresponding Author: Noresah Mohd Shariff Selection and peer-review under (Brunsdon et al, 2001), education (Fotheringham et al, 2001), marketing research (Mittal, Kamakura, & Govind, 2004), regional science (Huang & Leung, 2002), political science (Calvo & Escolar, 2003), and transport research (Nakaya, 2001;Lloyd & Shuttleworth, 2005;Zhao, Chow, Li, & Liu, 2005;Chow, Zhao, Liu, Li, & Ubaka, 2006;Du & Mulley, 2006;Clark, 2007). Moreover, GWR has been applied to examine regional variations in the link between environmental variables and socio-economic indicators and to investigate geographic heterogeneity in urban and regional growths (Yu, 2006;Partridge, Rickman, Ali, & Olfert, 2008).…”
Section: Problem Statementmentioning
confidence: 99%
“…In recent years, this model has been applied to research in the field of transportation and has provided many results [31][32][33][34]. In the research on public transportation ridership, Chow et al [35] applied a GWR model to predict bus passenger flow for home-based trips using data from Broward County, Florida. They found that the GWR model generates more accurate predictions than linear regression models.…”
Section: Application Of Gwr In the Transportation Fieldmentioning
confidence: 99%